Burkholderia glumae MA13: A newly isolated bacterial strain suitable for polyhydroxyalkanoate production from crude glycerol - Paula, Fabricio Coutinho de; Kakazu, Sergio [UNESP]; Chimello de Paula, Carolina Bilia [UNESP]; Almeida, Alex Fernando de; Cabrera Gomez, Jose Gregorio; Contiero, Jonas [UNESP] (Elsevier B.V., 2019)
Burkholderia glumae MA13 was isolated from soil samples of Atlantic rain forest ecosystem as a new bacterial strain for polyhydroxyalkanoate (PHA) production from crude glycerol as sole carbon source. Among 107 glycerol consuming bacterial isolates, B. glumae MA13 was cultivated in shake flask experiments in order to verify its PHA production capability from crude glycerol besides waste cooking oil and sugarcane molasses free of pretreatment, showing intracellular poly(3-hydroxybutyrate) [P(3HB)] accumulation values of 51.3, 51.4 and 49% of cell dry weight (CDW), respectively. The addition of propionic or hexanoic acids to the media containing crude glycerol resulted in the copolymers poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] comprised of up to 32.1 mol% of 3HV monomer or poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] with a maximum of 0.3 mol% of 3HHx, respectively. Fed-batch cultivation performed in a 10 L-scale bioreactor showed a maximum P(3HB-co-3HV) production of 9.9 g/L, which was 65.1% of total biomass and consisted of 21.8 mol% of 3HV monomer, with a maximum volumetric productivity of 0.22 g/(L h). The 3HV conversion yield achieved 1.04 g/g after 48 h cultivation, which was 76.7% of the maximum theoretical yield. B. glumae MA13 has showed to be an adapted bacterial strain to the synthesis of bioplastics from biofuel byproducts, and so from here it has been revealed as a promising PHA producer for an associated production set which has been considered as a prominent and ecologically friendly alternative to petrochemical plastics and fuels.
Keywords: Biodiesel; Bioplastic; Burkholderia glumae; Glycerol; Polyhydroxyalkanoates